Evolutionary transitions revisited: Holobiont evo‐devo. Issue 8 (29th September 2019) - Gilbert, Scott F.
Abstract: John T. Bonner lists four essential transformations in the evolution of life: the emergence of the eukaryotic cell, meiosis, multicellularity, and the nervous system. This paper analyses the mechanisms for those transitions in light of three of Dr. Bonner's earlier hypotheses: (a) that the organism is its life cycle, (b) that evolution consists of alterations of the life cycle, and (c) that development extends beyond the body and into interactions with other organisms. Using the notion of the holobiont life cycle, this paper attempts to show that these evolutionary transitions can be accomplished through various means of symbiosis. Perceiving the organism both as an interspecies consortium and as a life cycle supports a twofold redefinition of the organism as a holobiont constructed by integrating together the life cycles of several species. These findings highlight the importance of symbiosis and the holobiont development in analyses of evolution. Abstract : John T. Bonner has proposed (a) the organism is a life cycle, (b) evolution is the alterations of life cycles, and (3) development extends into interactions with other organisms. Together, these formulate a holobiont approach to development and evolution. HIGHLIGHTS: John T. Bonner has made three proposals that need to be taken seriously by evo‐devo: (a) the organism is a life cycle, (b) evolution is the alterations of life cycles, and (3) development extends to interactions with other organisms.